The Metaphorical Conceptualization of Emotions in the Secret History of the Mongols - Zolzaya Choijin, (Acta Mongolica, 2014)
This article investigates the emotion metaphors in the Secret History of the Mongols (SHM: 1227). Specifically, it examines the linguistic metaphorical expressions for the concepts of emotions such as anger, happiness, and sadness within the CMT framework. The culture/language-specific elaborations of conceptual metaphors are only grounded on cultural salience at a specific level in the given culture. Moreover, the study contributes importantly to understanding the value of the nomadic culture and its association with metaphors manifesting the emotion concepts by nomads in the 13th century. The speakers of Mongolian differ widely from those in other cultures in their centuries-long experience of nomadic lifestyles, interacting with animals, and social and physical environments.